2017
DOI: 10.1007/978-3-319-66182-7_34
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transport for Diffeomorphic Registration

Abstract: This paper introduces the use of unbalanced optimal transport methods as a similarity measure for diffeomorphic matching of imaging data. The similarity measure is a key object in diffeomorphic registration methods that, together with the regularization on the deformation, defines the optimal deformation. Most often, these similarity measures are local or non local but simple enough to be computationally fast. We build on recent theoretical and numerical advances in optimal transport to propose fast and global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 11 publications
0
74
0
Order By: Relevance
“…The theory of OT seeks the most feasible way to redistribute mass from one given distribution to another while minimizing the associated cost of transportation ( [9], [12]). OT has been used for registration and connectivity analysis of brain white matter [7], image morphing [4], and has recently been extended to the case of measures of different total mass [2].…”
Section: Introductionmentioning
confidence: 99%
“…The theory of OT seeks the most feasible way to redistribute mass from one given distribution to another while minimizing the associated cost of transportation ( [9], [12]). OT has been used for registration and connectivity analysis of brain white matter [7], image morphing [4], and has recently been extended to the case of measures of different total mass [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since δq and p are absolutely continuous, t → (p t | δq t ) is also absolutely continuous. We deduce from the expressions ofq t ,ṗ t , and δq t given by equations (20), (21), and (18) that…”
Section: Expression Of the Gradientmentioning
confidence: 99%
“…However, this reserve of mass can only be used at the ends of a geodesic path. In a recent work, Feydy et al [20] use unbalanced regularized optimal transport methods as a fidelity term for diffeomorphic registration purpose.…”
mentioning
confidence: 99%
“…Contribution. At MICCAI 2017, we introduced the theory of Optimal Transport to the medical imaging community [5]. Leveraging the ideas and algorithms presented in [11], we showed that using globally optimal spring systems to drive a registration routine is tractable, and improves the robustness of pipelines to large deformations.…”
Section: Introductionmentioning
confidence: 99%